2019
DOI: 10.1097/meg.0000000000001521
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological characteristics of Epstein-Barr virus-positive gastric cancer in Latvia

Abstract: Objective: Epstein-Barr virus (EBV)-associated gastric cancer (GC) has been proposed to be a distinct GC molecular subtype. The prognostic significance of EBV infection in GC remains unclear and needs further investigation. Our study aimed to analyze EBV-positive and EBV negative GC patients regarding their personal and tumor-related characteristics, and compare their overall survival.Methods: GC patients consecutively treated at the Riga East University Hospital during 2009-2016 were identified retrospectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…There was approximately average 10% EBV positive cases in GC samples worldwide (35,36). For Latvia GC population, EBV positivity was a favorable prognostic factor in GC while it had no significant difference in other relative large cohort (37). Not only the intrinsic alterations of MSI and EBV infected cells but also the tumor microenvironment (TME) contributes to these clinical characteristics to some extent.…”
Section: Discussionmentioning
confidence: 99%
“…There was approximately average 10% EBV positive cases in GC samples worldwide (35,36). For Latvia GC population, EBV positivity was a favorable prognostic factor in GC while it had no significant difference in other relative large cohort (37). Not only the intrinsic alterations of MSI and EBV infected cells but also the tumor microenvironment (TME) contributes to these clinical characteristics to some extent.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the estimated EBV positive rate was 11.3%. EBV positive rates ranged from 1.2% to 89.2% in the individual eligible studies [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , …”
Section: Discussionmentioning
confidence: 99%
“…In 2018, Panda et al (13) found EBV-positive gastric cancer with low mutation burden to be a subset of microsatellitestable (MSS) gastric cancer, which may respond to immune checkpoint therapy. Thus, EBVpositive gastric cancer is now considered a unique molecular subtype of gastric cancer (14) and is associated with good prognosis in patients (15). At present, there is no article to summarize and analyze the characteristics, mechanisms, and treatment of EBV-positive gastric cancer, including latency proteins.…”
Section: Introductionmentioning
confidence: 99%